2020
DOI: 10.1186/s13287-020-1576-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-495 confers inhibitory effects on cancer stem cells in oral squamous cell carcinoma through the HOXC6-mediated TGF-β signaling pathway

Abstract: Background: Oral squamous cell carcinoma (OSCC) is associated with high morbidity and ranks sixth among malignancies worldwide. Increasing evidence suggests that microRNAs (miRNAs or miRs) play a critical role in regulating cancer stem cells (CSCs), which drive the proliferation and spread of OSCC. Therefore, based on the alteration of aberrantly expressed miR-495 and homeobox C6 (HOXC6) by Gene Expression Omnibus (GEO) analysis, we subsequently explore the potential effect of miR-495 on the progression of CSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…9a). Previous studies reported that HOXC6 played a vital role in EMT [28][29][30]; therefore, it was chosen as the candidate. In addition, the dual-luciferase reporter assay was applied to confirm whether HOXC6 was a target for miR-27b-3p.…”
Section: Identification Of Candidate Genes Regulated By Mir-27bmentioning
confidence: 99%
“…9a). Previous studies reported that HOXC6 played a vital role in EMT [28][29][30]; therefore, it was chosen as the candidate. In addition, the dual-luciferase reporter assay was applied to confirm whether HOXC6 was a target for miR-27b-3p.…”
Section: Identification Of Candidate Genes Regulated By Mir-27bmentioning
confidence: 99%
“…The microRNA miR-495 is one that inhibits the expression of homeobox C6 and the function of TGF-β1. Its overexpression in CSCs contributes to EMT reversion, apoptosis, and the decreased proliferation and migration of CSCs [ 66 ]. The miRNA-200 family is another important group of microRNAs that promote cyst formation and ovarian cancer spread through targeting TGF-β expression [ 67 ].…”
Section: Tgf-β In Cancer Initiation and Progressionmentioning
confidence: 99%
“…[ 32 ] You has reported that miRNA-495 confers inhibitory effects on cancer stem cells in oral squamous cell carcinoma through the HOXC6-mediated TGF-β signaling pathway. [ 33 ] Similar to the TGF-β signaling pathway, Hippo signaling pathway dysregulation has been shown to contribute to the development of cancer. Martin confirmed that FAT1 acts as a tumor suppressor in HNSCC cells by inhibiting the Hippo signaling pathway.…”
Section: Discussionmentioning
confidence: 99%